Curve fitting technique for optimal pulsewidth modulation (PWM) online control of a voltage source inverter (VSI) - 217781 Naziha Ahmad Azli; Abdul Halim Mohamed Yatim, 1959-; International Conference of Intelligent System (2000 : Kuala Lumpur)
12